INCORPORATING ENVIRONMENT SUSTAINABILITY CONTENT IN TRANSLATION TEACHING THROUGH A TASK-BASED APPROACH - Siregar, Roswani; Nuraida, Nuraida; Kalsum, Eka Umi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Task-based teaching and learning is a boon approach in English classes nowadays to create a real practice for language use and provide a natural context for language study. This article exposes the use of task-based approach by incorporating environmental sustainability as content in translation practice. The tasks consist of three phases, pre-task, during-task, and post-task. Each phase is to enrich the student's experience in learning the novel terms along with the strategy for dealing with the difficult terms in the source text. The sample of the study is the students who participated in a translation course program from two universities. The total participants are 42 of 95 students who are available for this course session conducted in May 2022. Before pre-task, the students' preferences were collected to identify the students’ interest and expectations of the heading course. In during-task, students are asked to take notes based on their interests. After the pre-task, students presented their own experiences in completing the task. At the end of the course session, a questionnaire was given to investigate the advantage of the learning approach and students' experience in the translation course. It was observed that students use the target language to communicate with peers in doing assignments. The student's confidence, which is the key to acquiring a language, increased in using specific terms. Combination of task-based learning with appropriate content that is relevant to personal lives such as environmental sustainability increases the student's motivation to learn and benefit from the translation activity.